Timing is Almost Everything: Obstructionist Leadership, Cypriot Style - Rotberg, Robert (Tufts Archival Research Center, 2005)
Volume 28, Issue 2. Summer Robert Rotberg highlights the importance of timing in positive leadership positions, as seen through Rauf Denktashï¿½s role in the Cyprus negotiations.